ANALISIS PENDAPATAN USAHATANI PADI DENGAN METODE SALIBU DI DESA SUMBERSUKO JAYA KECAMATAN BELITANG KABUPATEN OKU TIMUR - Leni Sabrina, Andri Irawan, Iman Sulaiman, Anggi Fatmayati, (JASEP, 2025)
Salibu (Salin Ibu) is one of the new rice farming methods which is a form of innovation originating from the local wisdom of the community. This study aims to analyze the income of rice farming businesses using Salibu cultivation techniques. This study was conducted in Sumbersuko Jaya Village, Belitang District, East OKU Regency. The research method used in this study is the survey method. The sampling technique in this study used a census or saturated sample, namely 30 rice farmers who used Salibu cultivation techniques. The data used were processed using the income formula. The results of the study showed that the average income of Salibu rice farming was IDR 5,874,787.00/MT.